Corrosion resistance of stainless steel, nickel-titanium, titanium molybdenum alloy, and ion-implanted titanium molybdenum alloy archwires in acidic fluoride-containing artificial saliva: An in vitro study - Venith Jojee Pulikkottil; S Chidambaram; P U Bejoy; P K Femin; Parson Paul; Mohamed Rishad (Wolters Kluwer Medknow Publications, 2016)
Objective: (1) To evaluate the corrosion resistance of four different orthodontic archwires and to determine the effect of 0.5% NaF (simulating high fluoride-containing toothpaste of about 2250 ppm) on corrosion resistance of these archwires. (2) To assess whether surface roughness (Ra) is the primary factor influencing the corrosion resistance of these archwires. Materials and Methods: Four different archwires (stainless steel [SS], nickel-titanium [NiTi], titanium molybdenum alloy [TMA], and ion-implanted TMA) were considered for this study. Surface characteristics were analyzed using scanning electron microscopy, atomic force microscopy (AFM), and energy dispersive spectroscopy. Linear polarization test, a fast electrochemical technique, was used to evaluate the corrosion resistance, in terms of polarization resistance of four different archwires in artificial saliva with NaF concentrations of 0% and 0.5%. Statistical analysis was performed by one-way analysis of variance. Results: The potentiostatic study reveals that the corrosion resistance of low-friction TMA (L-TMA) > TMA > NiTi > SS. AFM analysis showed the surface Ra of TMA > NiTi > L-TMA > SS. This indicates that the chemical composition of the wire is the primary influential factor to have high corrosion resistance and surface Ra is only secondary. The corrosion resistance of all wires had reduced significantly in 0.5% acidic fluoride-containing artificial saliva due to formation of fluoride complex compound. Conclusion: The presence of 0.5% NaF in artificial saliva was detrimental to the corrosion resistance of the orthodontic archwires. Therefore, complete removal of residual high-fluorinated toothpastes from the crevice between archwire and bracket during tooth brushing is mandatory.